Application of electronic belt weigher in weighing of backfilled bulk gravel in vertical shaft - HU Hao; CHEN Silin; LIU Junpeng; LI Ying; LI Wenjie; YIN Liang (Gong-kuang zidonghua, 2014)
The paper introduced structure, working principle, method of installation and calibration of electronic belt weigher, and analyzed causes for error of the electronic belt weigher. Meanwhile, it also put forward methods of reducing errors in metering combined with usage experience of electronic belt weigher.